أهمية التربية الموسيقية في بناء شخصية الطفل - الككلي د. محمد سعيد (Aljameai, 2023)
المستخلص: الموسيقى جزءا من التربية الفنية التي تهدف إلى السمو بالمستوى الإنساني للفرد ولا شك أن العلاقة وثيقة بين التربية والموسيقى بحيث تلعب دوراً هاماً في بناء شخصية الطفل وهذا الان مفاهيمه تعتمد على كثيراً من الاساليب التربوية لتحقيق هذا الهدف وتحتوي حصة التربية الموسيقية على ثلاثة أنشطه وiي: - القواعد الموسيقية وتربية الصوت والتذوق الموسيقي. Abstract: Music is part of artistic education that aims to raise the human level of the individual. There is no doubt that the relationship is close between education and music, as it plays an important role in building the child’s personality. These concepts now depend a lot on educational methods to achieve this goal. The music education class contains three activities, namely: - Musical rules and education Voice and musical taste.